Methylation matters: binding of Ets-1 to the demethylated Foxp3 gene contributes to the stabilization of Foxp3 expression in regulatory T cells - Polansky, Julia K. (Springer-Verlag, 2010)
The forkhead-box protein P3 (Foxp3) is a key transcription factor for the development and suppressive activity of regulatory T cells (Tregs), a T cell subset critically involved in the maintenance of self-tolerance and prevention of over-shooting immune responses. However, the transcriptional regulation of Foxp3 expression remains incompletely understood. We have previously shown that epigenetic modifications in the CpG-rich Treg-specific demethylated region (TSDR) in the Foxp3 locus are associated with stable Foxp3 expression. We now demonstrate that the methylation state of the CpG motifs within the TSDR controls its transcriptional activity rather than a Treg-specific transcription factor network. By systematically mutating every CpG motif within the TSDR, we could identify four CpG motifs, which are critically determining the transcriptional activity of the TSDR and which serve as binding sites for essential transcription factors, such as CREB/ATF and NF-κB, which have previously been shown to bind to this element. The transcription factor Ets-1 was here identified as an additional molecular player that specifically binds to the TSDR in a demethylation-dependent manner in vitro. Disruption of the Ets-1 binding sites within the TSDR drastically reduced its transcriptional enhancer activity. In addition, we found Ets-1 bound to the demethylated TSDR in ex vivo isolated Tregs, but not to the methylated TSDR in conventional CD4(+) T cells. We therefore propose that Ets-1 is part of a larger protein complex, which binds to the TSDR only in its demethylated state, thereby restricting stable Foxp3 expression to the Treg lineage. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00109-010-0642-1) contains supplementary material, which is available to authorized users.